Evaluation of The Implementation of The Computer Based National Assessment in Indonesian School of Bangkok - Qomariah, Nurul; Sumardi, Sumardi; Muhibbin, Ahmad (Metodik Didaktik, 2024)
Starting with the final-stage assessment system for basic and secondary schools, problems continue to arise during the final stage of assessment. In addition, as Indonesia is affected by the COVID-19 pandemic, the problem requires learning activities to be implemented online. Starting in 2020, the Ministry of Education and Culture will transform the National Exam into a national computer-based assessment or Asesmen Nasional Berbasis Komputer (ANBK). This change shows a paradigm in the evaluation of primary and secondary education. The study was conducted at Indonesian School of Bangkok, Indonesian School Overseas located in Bangkok, Thailand. The aim of this study is to identify, describe, and formulate the evaluation of the implementation of ANBK at the primary school of Indonesian School of Bangkok. This study is expected to be used as a reference in the implementation of ANBK in the next year. This research method is qualitative descriptive in which data is obtained through active observation, open interviews, and documentation. The results of the research showed that the implementation of the ANBK at the Indonesian School of Bangkok went with the lancer despite several obstacles, including technical constraints and the level of concentration of students in working on the issue of the ANBK. The observation results also showed that there are students with a marriage background of citizens of Indonesia and foreign nationals  parents who reach the minimum limits of competence in literacy and numeration aspects, but character aspects have evolved.